2004
DOI: 10.1002/ana.20296
|View full text |Cite
|
Sign up to set email alerts
|

Increased D1 dopamine receptor signaling in levodopa‐induced dyskinesia

Abstract: Although supersensitivity of D 2 receptors is expected when parkinsonism is first apparent, the first L-dopa dose administered does not generally induce dyskinesia, but dyskinesia develops gradually over time.7 Accordingly, the D 2 /D 3 receptor agonists exert an antiparkinsonian effect with a reduced propensity to elicit dyskinesia when administered de novo in PD patients. 8 There is some evidence that D 1 messenger RNA (mRNA) levels are increased after dopaminergic treatment of the DA-depleted striatum in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
295
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(312 citation statements)
references
References 38 publications
13
295
1
3
Order By: Relevance
“…Remarkably, we found that SKF-81297 induced significantly more MD than apomorphine and quinpirole, what is consistent with reports showing that D1/D5 agonists increase oral movements in rats and monkeys with intact dopaminergic pathways (Bedard and Boucher, 1989;Waddington et al, 1995) and produce abnormal dyskinetic oral movements in MPTP-lesioned marmosets (Gnanalingham et al, 1995). Overall, these findings are well in line with recent research showing altered D1 receptor signaling in the striatum of parkinsonian rats (Gerfen et al, 2002) and MPTP monkeys rendered dyskinetic by chronic levodopa administration (Aubert et al, 2005), and further support the usefulness of rodent models of PD for the study of dopamine agonistinduced dyskinesia. There are reports regarding dopamine agonists' effects on striatal regional cerebral blood volume (rCBV) and BOLD in 6-OHDA-lesioned rats.…”
Section: D1/d5 Dopamine Receptor Agonists Are More Powerful Inductorssupporting
confidence: 92%
See 1 more Smart Citation
“…Remarkably, we found that SKF-81297 induced significantly more MD than apomorphine and quinpirole, what is consistent with reports showing that D1/D5 agonists increase oral movements in rats and monkeys with intact dopaminergic pathways (Bedard and Boucher, 1989;Waddington et al, 1995) and produce abnormal dyskinetic oral movements in MPTP-lesioned marmosets (Gnanalingham et al, 1995). Overall, these findings are well in line with recent research showing altered D1 receptor signaling in the striatum of parkinsonian rats (Gerfen et al, 2002) and MPTP monkeys rendered dyskinetic by chronic levodopa administration (Aubert et al, 2005), and further support the usefulness of rodent models of PD for the study of dopamine agonistinduced dyskinesia. There are reports regarding dopamine agonists' effects on striatal regional cerebral blood volume (rCBV) and BOLD in 6-OHDA-lesioned rats.…”
Section: D1/d5 Dopamine Receptor Agonists Are More Powerful Inductorssupporting
confidence: 92%
“…But the neural mechanisms of dopamine agonist-induced dyskinesia are thought to essentially concern the indirect pathway (Crossman, 1990;Obeso et al, 2000) and our findings suggest a primary involvement of the D1 receptor regulated direct pathway. A primary involvement of D1 receptors and the direct basal ganglia pathway is suggested by other recent studies too (Aubert et al, 2005;Fiorentini et al, 2006), and by the fact that D2 family agonists are less likely to induce dyskinesia in patients and animal models of PD than unselective and D1/D5 selective agonists (present findings; Gnanalingham et al, 1995;Blanchet et al, 1996;Pearce et al, 1999;Goulet and Madras, 2000;Nutt, 2000;Rascol et al, 2001;Lundblad et al, 2002;Monville et al, 2005). A recent study established that levodopa-induced dyskinesia in the rat 6-OHDA model is related to increased synchronization of afferent activity to the basal ganglia output nuclei (Meissner et al, 2006).…”
Section: Severity Of Fd Is Related To Striatal and Motor Cortex Bold mentioning
confidence: 64%
“…LID is associated with some characteristic neurochemical changes in the basal ganglia: it is dependent on the over-functioning of DA D 1 -like receptors in the striatopallidal MSNs (Aubert et al, 2005), leading to increased phosphorylation at threonine 34 of DARPP-32 and inhibition of PP-1 (Santini et al, 2007); this results in a loss of depotentiation and enhanced activation of the striatopallidal neurons (Picconi et al, 2003), typified increased to FosB expression (Pavon et al, 2006), which is currently considered the main neurophysiologic trait associated with LID in animal models of PD (Picconi et al, 2003, Santini et al, 2007. Active DARPP-32-Thr(34) enhances phosphorylation of NMDA receptors, which provides a rationale to understand the ability of Amantadine to achieve its long-term antidyskinetic effects, albeit its clinical use is limited by the side effects resulting from its interference with all forms of plasticity dependent on NMDA receptors (Lundblad et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Active DARPP-32-Thr(34) enhances phosphorylation of NMDA receptors, which provides a rationale to understand the ability of Amantadine to achieve its long-term antidyskinetic effects, albeit its clinical use is limited by the side effects resulting from its interference with all forms of plasticity dependent on NMDA receptors (Lundblad et al, 2005). Further adding to this dyskinesia-associated unbalanced regulation of DARPP-32, a key integrator of the responsiveness of MSNs (Picconi et al, 2003), dyskinetic animals also present higher levels of cdk5 in the striatum (Aubert et al, 2005), which phosphorylates DARPP-32 at threonine 75 and converts DARPP-32 into an inhibitor of protein kinase A (PKA) (Picconi et al, 2003, Santini et al, 2007. The pharmacological and genetic manipulations to reduce the phosphorylation of DARPP-32 or PKA activity were also successful in alleviating dyskinesia in hemiparkinsonian animals (Santini et al, 2007, Darmopil et al, 2009, Lebel et al, 2010.…”
Section: Discussionmentioning
confidence: 99%
“…56 In addition, increased D1 receptor signaling has also been shown to occur in animal models of levodopainduced dyskinesias. 57 Not surprisingly, the development of dyskinesias in animal models of PD requires the same drug schedule as that necessary to induce psychomotor sensitization by psychostimulants. 58 Stereotypies.…”
Section: Methods and Review Criteriamentioning
confidence: 99%